Demand for public events in the COVID-19 pandemic: A case study of European football - Reade, J. J.; Singleton, C. (SSRN, 2020)
We use data from elite-level European football matches to suggest how people responded to the initial COVID-19 outbreak. Unsurprisingly, in Italy, France and England, stadium attendances were negatively affected by the previous day's newly confirmed domestic cases or deaths. In Germany, there was no response to the early stages of the domestic or worldwide outbreak. Spain poses a puzzle, as attendances appear to have increased substantially in response to the initial domestic deaths related to the virus.